Perceptions of Public Health Priorities and Accountability Among US Mayors. (March 2021) - Godinez Puig, Luisa; Lusk, Katharine; Glick, David; Einstein, Katherine L.; Palmer, Maxwell; Fox, Stacy; Wang, Monica L.
Objective: Mayors have considerable and often direct influence over health policy in their cities, yet little is known about mayors' general perceptions of current public health challenges. The objective of this study was to assess perceptions, attitudes, and priorities related to public health among US mayors. Methods: We collected survey data from a nationally representative sample of US mayors (N = 110) in 2018 and matched survey responses with city-level health surveillance data. We conducted descriptive analyses and multivariable regression modeling to estimate associations of interest. Results: Mayors in our sample most frequently cited obesity/chronic diseases (23.6%; 26 of 110), opioid abuse/drug addiction (22.7%; 25 of 110), and health care access (13.6%; 15 of 110) as the top health challenges facing their cities. However, mayors identified a different set of health issues for which they believed constituents hold them accountable. With the exception of opioid-related deaths, prevalence of a health concern was not associated with perceived accountability for that particular issue, whereas partisanship and sex predicted patterns in perceived accountability. Conclusions: Mayors recognized critical health challenges at the city level but varied widely in their perceived accountability for such challenges. Findings can inform strategies to engage local policy makers in cross-sector collaborations to improve the health and overall well-being of people in cities across the United States.